Recession, precariousness and inequality: youth employment trajectories before and after the 2008-2009 recession - Williamson, Stefanie (2018)
The extent of youth unemployment in the UK in the years following the 2008 economic crisis, as well as the backdrop of longer-term concern regarding the rise of precarious work (Beck 2000, Standing 2011) prompted discussions of a ‘lost generation’ of young people set to feel the economic scars from embarking on their careers at a time of economic turmoil. The 2008-2009 recession was also (dubiously) labelled a ‘mancession’ and the first ‘middle class recession’. Despite this, comparatively few sociology studies have adopted a quantitative approach to compare the class and gender dimensions of inequality in young people’s employment trajectories prior to and following the 2008-2009 recession. This research makes an original contribution to the field by using longitudinal sequence analysis methods to contrast the employment trajectories of two cohorts of 16 to 24 year olds in the UK: a pre-recession and a recession cohort. In doing so, it establishes the extent to which the patterns of class and gender inequality amongst young people, not only in unemployment, but also in the movement in and out of ‘precarious work’, differed prior to and following the 2008-2009 recession. It finds that precarious employment was not as widespread as ‘end of work’ theorists suggested but that the recession brought an increased minority of young people who experienced employment difficulty. Furthermore, it argues that the recession did not advantage or disadvantage class or gender groups in a uniform way. Rather, changing trends in the recession highlighted a number of complex and shifting patterns of inequality amongst young people of different genders and from differing class backgrounds.